2012
DOI: 10.1017/s0269888912000227
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory deconfliction with constraint programming

Abstract: As acknowledged by the SESAR (Single European Sky ATM (Air Traffic Management) Research) program, current Air Traffic Control (ATC) systems must be drastically improved to accommodate the predicted traffic growth in Europe. In this context, the Episode 3 project aims at assessing the performance of new ATM concepts, like 4D-trajectory planning and strategic deconfliction.One of the bottlenecks impeding ATC performances is the hourly capacity constraints defined on each en-route ATC sector to limit the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…It is hypothesized that the pre-planning scheduler outperforms the baseline scheduler when the take-o↵ time estimates are perfect (hypothesis 2-1). In a previous study, Barnier and Allignol found that for aircraft deconfliction, incorporating flights prior to departure was not e↵ective with departure time uncertainties of three minutes [18]. It was therefore hypothesized that for pre-planning of pop-up flights to be e↵ective, the departure time uncertainty needs to be smaller than three minutes (hypothesis 2-2).…”
Section: B Hypothesesmentioning
confidence: 98%
“…It is hypothesized that the pre-planning scheduler outperforms the baseline scheduler when the take-o↵ time estimates are perfect (hypothesis 2-1). In a previous study, Barnier and Allignol found that for aircraft deconfliction, incorporating flights prior to departure was not e↵ective with departure time uncertainties of three minutes [18]. It was therefore hypothesized that for pre-planning of pop-up flights to be e↵ective, the departure time uncertainty needs to be smaller than three minutes (hypothesis 2-2).…”
Section: B Hypothesesmentioning
confidence: 98%
“…For the case of a medium jet-propelled aircraft in the en-route phase, this results in validation time interval of 12 15 seconds, as it is the time that in the worst case scenario of two aircraft travelling 500 knots ground speed would take to travel the separation distance of 5 nautical miles 21 . The 4-PNV model is also used in the Terminal Manoeuvring Area (TMA), with reduced separation minima and varying manoeuvres and contrasting speeds.…”
Section: Intent Validationmentioning
confidence: 99%
“…t is chosen small enough to detect every significant conflict in the application. Only conflicts at the fringe of the detection volume and lasting less than t seconds could be missed, as indicated by the formula (detailed in [Barnier and Allignol, 2012]:…”
Section: Maneuversmentioning
confidence: 99%